PENGARUH KELENGKAPAN PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA PT. SULO RANTEPAO TORAJA UTARA - Antasya Eka Putri Eka Putri; Abedneigo C. Rambulangi; Lisa. K. Wibisono (ITB AAS Indonesia Surakarta, 2026)
This study aims to determine and analyze the effect of product completeness (X1) and service quality (X2) on purchasing decisions at PT. Sulo Rantepao, North Toraja. The research employs a quantitative approach using multiple linear regression analysis. Data were collected through the distribution of questionnaires to 97 respondents. The results show that, partially, the product completeness variable (X1) does not have a significant effect on purchasing decisions, as indicated by a significance value of 0.099 > 0.05 and a t-value of 1.667 < the t-table value of 1.985. Meanwhile, the service quality variable (X2) is proven to have a positive and significant effect on purchasing decisions, with a significance value of 0.00 < 0.05 and a t-value of 8.540 > the t-table value of 1.985. Simultaneously, product completeness (X1) and service quality (X2) have a significant effect on purchasing decisions (Y), as evidenced by a significance value of 0.00 < 0.05 and an F-value of 77.331 > the F-table value of 3.09. The R-squared value of 0.614 indicates that the two independent variables are able to explain 61.4% of the variation in purchasing decisions, while the remaining 38.6% is influenced by other variables outside this study. Keywords: Product Assortment Completeness, Service Quality, Purchasing Decision, Multiple Linear Regression